Pengaruh Orientalis terhadap Liberalisasi Pemikiran Islam - Abbas Mansur Tammam (Universitas Darussalam Gontor, 2016)
The liberalization of Islamic thought, which is considered and proclaimed as “renewal of Islamic thought,” did not come from the core concepts of Islam, it came from the outside of Islamic concepts (read: Western). Initially, the Western-Christian liberalism is an extension of the sophism, with ever implicated in Greece. Among the important figures is Heraclitus, Democritos and Protagoras. Although they received fierce opposition from Socrates, Plato and Aristotle, but liberalism got a new fresh air in the heyday of the Roman. This sophism trend, later gave birth to the relativism of truth, which is also the spirit of liberalism itself. Worse, liberalism was brought to Islam, the emergence of which can be traced to the Arabian Peninsula, Albania, and Syria. While in Egypt, Sultan Abdul Hamid II gave a note that a few Egyptian stunned with Western ideas, taking liberalism as a way of salvation. By using justifications of Qur’anic verses and hadiths, interpreted unilaterally, the liberalist thought was a tajdid to Islamic thought. The spirit (power) of liberalism is in the distribution process of using old methods, that is the tradition of orientalism, misionarism, and imperialism. The basis of liberalist support can be traced to some of the states concerned with it, such as the United States, Britain and France. Finally, this simple article will briefly try to uncover how this all happened.